Developing herbal mosquito repellent cotton fabric using the optimized process variables for the safe environment. (2023) - Pavan, M; Rani, Anita; Jhang, Tripta; Singh, SP
Abstract: Mosquito-repellent textiles offer protection from mosquito bites, thereby keeping the user safe. Using an herbal mosquito repellent extract on textile material could prompt protection from mosquitoes along with safety for both users and the environment. So, this study was under taken to develop an herbal mosquito repellent finish for cotton fabric using optimized process variables. The active component was extracted from different parts of the Anacyclus pyrethrum ( Akarkara ) plant, applied on cotton fabric samples and assessed for mosquito repellency. The highest mosquito repellency was observed in cotton fabric samples finished with Akarkara flower extract. The process parameters (conc. of the extract, material to liquor ratio and treatment time) were optimized using Box and Behnken Design of RSM to apply Akarkara flower extract on cotton fabric directly. To select the optimized variables, the finished fabrics were assessed for mosquito repellency (laboratory cage test method). Experimental work revealed that the mosquito repellency of finished cotton fabric samples was noted in a range of 57.87 percent to 79.63 percent in the 17 cotton fabric samples prepared as per the BBD matrix. The optimized concentration of the extract (15 %), MLR (1:20) and treatment time (30 min) were used for finishing the cotton fabric samples. It was observed that mosquito repellency increased with increasing concentration of the extract. The mosquito repellency of the finished cotton fabric sample was reduced to 24.2 percent from 79.5 percent upon one wash cycle and decreased further on every wash. Additionally, eight months old extract's from Akarkara flower, when applied on a cotton fabric surface, displayed a reduced mosquito repellency as compared to fresh extract application. Henceforth, through this kind of finish, an individual can receive protection from mosquito bites and further reduce cases of deadly diseases.